2018
DOI: 10.1101/458091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular Electron Uptake by TwoMethanosarcinaSpecies

Abstract: 9Direct electron uptake by prokaryotes is a recently described mechanism with a potential application for 10 energy and CO 2 storage into value added chemicals. Members of Methanosarcinales, an 11 environmentally and biotechnologically relevant group of methanogens, were previously shown to 12 retrieve electrons from an extracellular electrogenic partner performing Direct Interspecies Electron 13 45 (Holmes et al., 2018b; Shrestha et al., 2013). Geobacter's requirement for outer-surface proteins during 46 D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 68 publications
(67 reference statements)
1
20
0
Order By: Relevance
“…G. metallireducens, G. hydrogenophilus and R. ferrireducens were maintained on the typical co-culture freshwater media 10 with 55 mM ferric citrate as electron acceptor. The two Geobacter species were maintained with 10-20 mM ethanol as electron donor 11,12 whereas Rhodoferax was maintained with 5 mM glucose. P. carbinolicus which was used as H 2 -donating strain (DIET-negative control), was pre-cultivated under fermentative conditions on 10 mM acetoin as previously described 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…G. metallireducens, G. hydrogenophilus and R. ferrireducens were maintained on the typical co-culture freshwater media 10 with 55 mM ferric citrate as electron acceptor. The two Geobacter species were maintained with 10-20 mM ethanol as electron donor 11,12 whereas Rhodoferax was maintained with 5 mM glucose. P. carbinolicus which was used as H 2 -donating strain (DIET-negative control), was pre-cultivated under fermentative conditions on 10 mM acetoin as previously described 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Methanothrix soehengii, Methanosaeta harundinacea, Methanospirilum hungatei and Methanoculleus marisnigri were pre-grown on the typical co-culture freshwater media however without ethanol 10 Prior to co-cultivation, all Methanosarcina cultures were pre-grown on their respective substrates (20-30 mM acetate and/or 20 mM methanol) in a modified DSMZ 120c media in which tryptone was omitted and NaCl was reduced down to 1 g/L 11,12 . M. mazei (wild type and 633 k.o.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By inference we propose that Methanosarcina might be able to retrieve electrons directly from Fe 0 . This is because we recently reported that Methanosarcina barkeri could retrieve electrons directly from a poised cathode at −400 mV under conditions unfavorable for abiotic H 2 -evolution [23]. The same Methanosarcina was previously shown to grow on Fe 0 (although assumedly using H 2 ) [24] retrieve electrons from electrogenic syntrophic partners [25,26] or via electrically conductive particles [2729].…”
Section: Introductionmentioning
confidence: 99%